Job involvement, commitment, satisfaction and turnover: Evidence from hotel employees in Cyprus - Zopiatis, Anastasios; Constanti, Panayiotis; Theocharous, Antonis L. (My University, 2014)
The study of attitudes at work seeks to enhance organizational knowledge and capabilities in developing an ‘ideal’ working environment that delivers exceptional customer service. The current study investigates the causal relationships of job involvement, organizational commitment (normative and affective), and job satisfaction (intrinsic and extrinsic), with the intention of hospitality employees in Cyprus to either remain at or leave their job. Utilizing structural equation modeling, positive associations were found between job involvement, affective and normative commitment, and intrinsic job satisfaction. Positive associations between affective and normative organizational commitment, and intrinsic and extrinsic job satisfaction were also found. In addition, negative associations between affective organizational commitment, extrinsic job satisfaction and turnover intention were revealed. However, a negative association between intrinsic job satisfaction and turnover intention was not supported. The implications of these results for future research are also discussed.
Keywords: Cyprus; Turnover intention; Job satisfaction; Job involvement; Organizational commitment; SEM